2021
DOI: 10.1007/s40812-021-00182-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pandemics: revising the Spanish Flu in Italy in light of models’ predictions, and some lessons for the Covid-19 pandemic

Abstract: We consider some descriptive analysis of the main short- and medium-term economic indicators in Italy in the aftermath of the Spanish Flu pandemic. We analyse them in the light of the main neoclassical macroeconomic models of pandemics. Since most of the existing economic models about the consequences of a pandemic deal the pandemic event merely as a negative labour supply shock, we observe that some predictions of the theory about the economic impact of a pandemic seem not to be confirmed in the case of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…If a pandemic disproportionately affects the younger age group who are active contributors to the economy, it further increases the damage [10]. To avoid exposure to the virus, individuals reduce their interaction with suppliers, reducing the demand for goods and services that require close contact with persons [54]. Non-pharmaceutical interventions such as nationwide lockdowns, though necessary to stop the spread, affect the livelihoods of millions of people globally.…”
Section: Economic Impactsmentioning
confidence: 99%
“…If a pandemic disproportionately affects the younger age group who are active contributors to the economy, it further increases the damage [10]. To avoid exposure to the virus, individuals reduce their interaction with suppliers, reducing the demand for goods and services that require close contact with persons [54]. Non-pharmaceutical interventions such as nationwide lockdowns, though necessary to stop the spread, affect the livelihoods of millions of people globally.…”
Section: Economic Impactsmentioning
confidence: 99%
“…1 For instance, the dispute about of the impact of the Black Death pandemic -by large the most devastating pandemic in the human history -is mainly due to the difficulty of having uncontroversial data (see for instance Munro, 2009). 2 See Berbenni and Colombo (2021) for a comprehensive discussion of the main macroeconomic models which are used to model pandemics. 3 Such a negative impact of the pandemic on the growth rate of the economy in the absence of saving and fertility variations could be basically imputed to the decreasing returns of capital accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The Spanish Flu episode represents a useful test to discuss the modelling approach of pandemics: in the light of the historical evidence provided by the Spanish Flu, could a pandemic be simply interpreted as a negative labour shock? This approach has been questioned for example by Berbenni and Colombo (2021), where, by using a descriptive analysis of several macroeconomic variables in the post-pandemic period, it is shown that the impact of the Spanish Flu in Italy has been quite different from what predicted by theoretical models. A similar conclusion is reached also by Karlsson et al (2014), which, by looking to Swedish data in the post Spanish Flu period, find no evidence of real wage variations, in contrast to the predictions of theoretical models that suggest an increase of the real wage because of the scarcity of labour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation